Five new species of Heteropoda Latreille, 1804 spiders (Araneae: Sparassidae) from Southeast Asia - Korai, Shakal Khan; Jäger, Peter (Zootaxa, 2024)
Five new species of Heteropoda (Araneae: Sparassidae, Heteropodinae) from Southeast Asia are described: H. acris spec. nov. (male, female; Vietnam), H. cuspidata spec. nov. (male; Malaysia), H. papilionacea spec. nov. (female; Malaysia), H. pilata spec. nov. (female; Thailand), and H. verticalis spec. nov. (male; Malaysia). The female of H. jasminae Jäger, 2008 is described for the first time (locality: Vietnam). All these new species are diagnosed, described, and illustrated. Additionally, a distribution map for all species is given.